THE EFFECT OF GROUP COGNITIVE-BEHAVIORAL THERAPY ON DEPRESSION IN MENOPAUSAL WOMEN: A RANDOMIZED CLINICAL TRIAL : Pharmaceutical Sciences-Medicine - SOORI, MARZIE; KOLIVAND, MITRA; ABOLFATHI MOMTAZ, YADOLLAH; SALARI, NADER (International Journal of Life Science and Pharma Research, 2018)
Psychological and cognitive consequences of menopause such as irritability, stress, anxiety, feelings of sadness, mood changes, and depression affect quality of life of women in this period. Doing consultation with female patients to help them to cope with these changes can be useful. The current study was done to assess the effect of cognitive behavioral therapy (CBT) on depression in menopausal women in Tooiserkan, Iran.In this randomized clinical trial, 76 menopausal women who presented to health centers of Tooiserkan, Iran from September to December 2016 were included. Six CBT sessions were held. The Depression, Anxiety, and Stress Scale (DASS-21) was applied. After completing six CBT sessions, and also one month later the measurements were done. The data were analyzed using the Mann-Whitney and Friedman tests.Comparisons of depression scores between the two groups before initiating CBT was not significant (P> 0.05). Within-group comparisons of depression scores before and after CBT and one month later showed significant changes in CBT group (P< 0.001). These changes in control group were not significant (P> 0.05). It is suggested to use CBT for menopausal women to improve the quality of life of this group.